Yellow fever and traveling athletes: Is competing in Brazil safe? - Vancini, R. L.; Andrade, M. S.; Vancini-Campanharo, C. R.; Barbosa de Lira, C. A. (Journal of Human Kinetics, 2017)
It is acceptable to assume that the sport events globalization and increased mobility of elite athletes to endemic regions of infectious and viral diseases pose a risk to athletes and travelers. The risk of infectious diseases can be even higher in elite athletes due to their intense travel routine (Gärtner and Meyer, 2014) added to the exposure to different types of the environment where these athletes train (Turbeville et al., 2006).